1984
DOI: 10.1086/184226
|View full text |Cite
|
Sign up to set email alerts
|

Infrared galaxies in the IRAS minisurvey

Abstract: A total of 86 galaxies have been detected at 60 µm in the high galactic latitude portion of the IRAS minisurvey. The surface density of detected galaxies with flux densities greater than 0.5 Jy is 0.25 deg-2 • Virtually all the galaxies detected are spiral galaxies and have an infrared to blue luminosity ratio ranging from 50 to 0.5. For the infrared-selected sample, no obvious correlation exists between infrared excess and color temperature. The infrared flux from 10 to 100 µm contributes approximately 5% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
136
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(138 citation statements)
references
References 3 publications
2
136
0
Order By: Relevance
“…The majority of local IRAS-selected and ISO-selected galaxies were infrared galaxies with infrared luminosities within 10 11 < L IR < 10 12 L , though a small subset (∼12 galaxies) were ultraluminous infrared galaxies, or ULIRGs, with 10 12 < L IR < 10 13 L . Careful analysis of these galaxies, from studying their morphological structure in the optical, near-infrared, molecular gas and dust emission, indicated that the majority of systems above ∼10 11.5 L −or above star formation rates ∼50 M yr −1 −were major mergers of two or more equalmass galaxies Soifer et al 1984;Lonsdale et al 1984;Joseph & Wright 1985;Veilleux et al 2002, for a review, see Sanders & Mirabel, 1996).…”
Section: Local Infrared-luminous Galaxiesmentioning
confidence: 99%
“…The majority of local IRAS-selected and ISO-selected galaxies were infrared galaxies with infrared luminosities within 10 11 < L IR < 10 12 L , though a small subset (∼12 galaxies) were ultraluminous infrared galaxies, or ULIRGs, with 10 12 < L IR < 10 13 L . Careful analysis of these galaxies, from studying their morphological structure in the optical, near-infrared, molecular gas and dust emission, indicated that the majority of systems above ∼10 11.5 L −or above star formation rates ∼50 M yr −1 −were major mergers of two or more equalmass galaxies Soifer et al 1984;Lonsdale et al 1984;Joseph & Wright 1985;Veilleux et al 2002, for a review, see Sanders & Mirabel, 1996).…”
Section: Local Infrared-luminous Galaxiesmentioning
confidence: 99%
“…The importance of gas dynamics and triggered star formation in mergers is reinforced by observations of ultraluminous infrared galaxies (ULIRGs; e.g., Soifer et al 1984aSoifer et al , 1984b, which are invariably associated with mergers in the local universe (Joseph & Wright 1985;Sanders & Mirabel 1996). The infrared emission from ULIRGs is thought to be powered by intense starbursts in their nuclei, originating in central concentrations of gas (e.g., Scoville et al 1986;Sargent et al 1987Sargent et al , 1989, which will leave dense stellar remnants ( Kormendy & Sanders 1992;Hibbard & Yun 1999;Rothberg & Joseph 2004), as predicted theoretically (Mihos & Hernquist 1994c).…”
Section: Introductionmentioning
confidence: 99%
“…The significance of galaxies with an infrared excess was highlighted early by Low & Kleinmann (1968) and Rieke & Low (1972), and lately recognized by observations of the IRAS satellite (Soifer et al 1984). Among the sources that emit the bulk of their energy in the infrared, the Ultra-Luminous Infrared Galaxies (ULIRGs, 10 12 L ≤ L bol ∼ L IR [8-1000 μm] ≤ 10 13 L ), are amongst the brightest objects in the local Universe (see reviews in Lonsdale et al 2006;Sanders & Mirabel 1996).…”
Section: Introductionmentioning
confidence: 99%